2023
DOI: 10.1002/ente.202200943
|View full text |Cite
|
Sign up to set email alerts
|

Review of Potential‐Induced Degradation in Bifacial Photovoltaic Modules

Abstract: Bifacial modules are increasingly deployed in the field and are expected to represent half of the market share within 10 years. Their rear structure differs from monofacial modules to allow additional light absorption. However, it brings new reliability challenges to address. In particular, the risk of potential‐induced degradation (PID) is increased as both module sides are impacted. Different PID processes have been identified in the literature: shunting type (PID‐s), polarization type (PID‐p), Na penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…Given the interplay of these mechanisms, addressing each one individually poses challenges. Recent research on bifacial PV modules has shown that multiple PID mechanisms coexist 21 . Furthermore, Na‐driven PID has also been reported in Cu(In,Ga)(Se,S) 2 (CIGS) thin‐film solar cells 22–29 and recently in perovskite solar cells 30–34 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Given the interplay of these mechanisms, addressing each one individually poses challenges. Recent research on bifacial PV modules has shown that multiple PID mechanisms coexist 21 . Furthermore, Na‐driven PID has also been reported in Cu(In,Ga)(Se,S) 2 (CIGS) thin‐film solar cells 22–29 and recently in perovskite solar cells 30–34 .…”
Section: Introductionmentioning
confidence: 92%
“…Recent research on bifacial PV modules has shown that multiple PID mechanisms coexist. 21 Furthermore, Na-driven PID has also been reported in Cu(In,Ga)(Se,S) 2 (CIGS) thin-film solar cells [22][23][24][25][26][27][28][29] and recently in perovskite solar cells. [30][31][32][33][34] Therefore, this study aims to investigate and mitigate the fundamental cause of Na ingress to address PID concerns.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies, there has been a focus on the improvement of solar-cell materials to prevent PID [10,11], especially crystalline silicon solar cells [12,13]; thus, control of the base resistivity of materials is one of the methods to reduce PID. Earlier studies have pointed out that the PID problem can be effectively slowed down [14] when the base resistivity is higher.…”
Section: Basic Knowledge Related and Research Motivation Of The Studymentioning
confidence: 99%
“…Potential‐induced degradation (PID) occurs when charges migrate under an electric field associated with system voltage potential, accelerated by moisture and elevated temperature, leading to power loss and sometimes delamination in the module package. The reader is referred to several reviews in the literature for more information about the various degradation mechanisms of PID 1–3 . Polarization‐type PID (PID‐p) in Si cell technologies occurs when charge drifts within the passivating dielectric antireflective coating toward or away from the Si in such a way that it increasingly electrostatically attracts photogenerated carriers in the Si to the dielectric interface promoting their recombination, resulting in a loss of photocurrent and cell voltage 4,5 .…”
Section: Introductionmentioning
confidence: 99%